Cycling performance is superior for time-to-exhaustion versus time-trial in endurance laboratory tests - Coakley, S. L.; Passfield, L. (Journal of Sports Sciences, 2018)
Time-to-exhaustion (TTE) trials are used in a laboratory setting to measure endurance performance. However, there is some concern with their ecological validity compared with time-trials (TT). Consequently, we aimed to compare cycling performance in TTE and TT where the duration of the trials was matched. Seventeen trained male cyclists completed three TTE trials at 80, 100 and 105% of maximal aerobic power (MAP). On a subsequent visit they performed three TT over the same duration as the TTE. Participants were blinded to elapsed time, power output, cadence and heart rate (HR). Average TTE was 865 ± 345 s, 165 ± 98 s and 117 ± 45 s for the 80, 100 and 105% trials respectively. Average power output was higher for TTE (294 ± 44 W) compared to TT (282 ± 43 W) at 80% MAP (P < 0.01), but not at 100 and 105% MAP (P > 0.05). There was no difference in cadence, HR, or RPE for any trial (P > 0.05). Critical power (CP) was also higher when derived from TTE compared to TT (P < 0.01). It is concluded that TTE results in a higher average power output compared to TT at 80% MAP. When determining CP, TTE rather than TT protocols appear superior.